Representation of “Sapa Nandur Ngundhuh” in the Wayang Performance of Cupu Manik Astagina by Ki Enthus Susmono: Representasi “Sapa Nandur Ngundhuh” dalam Pergelaran Wayang Lakon Cupu Manik Astagina oleh Ki Enthus Susmono - Ida Fariha; Sucipto Hadi Purnomo (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Wayang kulit not only functions as entertainment, but is also a vehicle for conveying philosophical messages. As in the Cupu Manik Astagina puppet play, there is a philosophical message in the form of "sapa nandur ngundhuh" or whoever plants will reap. Therefore, this study aims to explore the philosophical message of "sapa nandur ngundhuh" in the Cupu Manik Astagina puppet play by Ki Enthus Susmono by representing it so that the message can be conveyed. This qualitative research uses Stuart Hall's representation theory through Roland Barthes' semiotic analysis model, namely symbolic code and action code. The data source is a video of a shadow puppet performance entitled "Pakeliran Solid Wayang Kulit Lakon Cupu Manik Astagina by Ki Enthus Susmono" on YouTube Aa Studio. The listening-note taking technique is used to collect data in the form of words and utterances obtained from ginem and janturan in the story. It is known through the symbol code and action code. The results showed that the concept of "sapa nandur ngundhuh" in the Cupu Manik Astagina puppet play does not only apply to the karma themselves, but can affect other people, including their descendants. In the story of Dewi Windradi, her actions have consequences not only for herself, but also her three children. This research also highlights how karma can be prevented from continuing to reap through some tirakat practices. Such as fasting (ngrowot), meditation and asceticism (tapa brata) which aim to cleanse themselves of past sins and minimize negative karma in the future.